Wind turbulence parameters from three dimensional full-scale measurements at 344 m high guyed mast site Gartow 2. Issue 172 (January 2018) - Höbbel, Thomas; Thiele, Klaus; Clobes, Mathias
Abstract: The behavior of structures due to gusty wind loads can be analyzed using statistical concepts in the frequency domain or in the time domain. In both cases, the knowledge about the temporal correlation of the turbulent wind speed in the atmospheric boundary layer at spatially adjacent points is required, especially for large structures such as long-span bridges. In a current project at the Institute of Steel Structures, a new extended wind measuring system based on 48 3D ultra-sonic anemometers is being installed along the guys of a 344 m high measurement mast, with first measured data already available. The probes follow a conical distribution. The measured data will be evaluated regarding to their temporal correlations in the time and frequency domain. The estimated turbulence parameters such as integral time scales and standard deviations of all three turbulence components from more than 2500 10-min. time series in the period from June to August 2015 are presented. It can be demonstrated that the estimated auto spectral density functions of all three turbulence components are in a good agreement with the von Kármán and Dryden models. The estimated cross correlation functions are also in a good agreement with the theoretical model functions. Highlights: 48 3D ultra-sonic anemometers installed on a 344 m high measurement mast. The estimated turbulence parameters of all three turbulence components are presented. Direct description of the cross-correlation functions (ccf) is proposed. The estimated ccf are in a good agreement with the proposed model functions.